Accurate prediction of interfacial residues in two‐domain proteins using evolutionary information: Implications for three‐dimensional modeling. Issue 7 (6th December 2013) - Bhaskara, Ramachandra M.; Padhi, Amrita; Srinivasan, Narayanaswamy
ABSTRACT With the preponderance of multidomain proteins in eukaryotic genomes, it is essential to recognize the constituent domains and their functions. Often function involves communications across the domain interfaces, and the knowledge of the interacting sites is essential to our understanding of the structure–function relationship. Using evolutionary information extracted from homologous domains in at least two diverse domain architectures (single and multidomain), we predict the interface residues corresponding to domains from the two‐domain proteins. We also use information from the three‐dimensional structures of individual domains of two‐domain proteins to train naïve Bayes classifier model to predict the interfacial residues. Our predictions are highly accurate (∼85%) and specific (∼95%) to the domain–domain interfaces. This method is specific to multidomain proteins which contain domains in at least more than one protein architectural context. Using predicted residues to constrain domain–domain interaction, rigid‐body docking was able to provide us with accurate full‐length protein structures with correct orientation of domains. We believe that these results can be of considerable interest toward rational protein and interaction design, apart from providing us with valuable information on the nature of interactions. Proteins 2014; 82:1219–1234. © 2013 Wiley Periodicals, Inc.